Konsep Nilai Budi Pekerti dalam Layanan Bimbingan Konseling Pendidikan Islam - Mohamad Syafiq; Fajar Putrawan Tanjung (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: The Concept of Ethical Values in Islamic Education Counseling Guidance ServicesCharacter is an individual's special character or character in acting politely and respecting other parties which can be seen from behavior in life. Meanwhile, character is all of an individual's attitudes, drives, habits, decisions, and good moral values which include the term policy. The research objectives in writing this thesis are 1. To find out the concept of moral values in Islamic counseling guidance services for students 2. To find out the factors inhibiting and supporting the concept of moral values in Islamic counseling guidance services for students 3. Knowing the results of the concept of moral values character in Islamic guidance and counseling services for students. The results of this research are that the implementation of Islamic counseling in moral development at MTSN 1 Kuala Tungkal, Tanjug, West Jabung Regency has been implemented and shows positive things. This can be seen from the changes that occur in each student. Gradually, students are able to carry out advice, directions and explanations from the guidance and counseling teacher, so that problems that have occurred do not occur again. Students who have attended Islamic counseling know more about their identity as human beings who have good character in everyday life, including the environment. school, family and neighborhood.Abstrak: Konsep Nilai Budi Pekerti dalam Layanan Bimbingan dan Konseling Pendidikan IslamBudi pekerti ialah tabiat ataupun watak khusus individu dalam bertindak sopan serta menghargai pihak lainnya yang terlihat dari perilaku dalam kehidupan. Sedangkan watak ialah semua sikap, dorongan, kebiasaan, keputusan, serta baiknya nilai moral individu yang mencangkup istilah dari kebijakan. Tujuan Penelitian dalam penulisan skripsi ini adalah 1. Untuk mengetahui konsep nilai budi pekerti dalam layanan bimbingan konseling Islam terhadap siswa 2. Untuk mengetahui faktor-faktor penghambat dan pendukung konsep nilai budi pekerti dalam layanan bimbingan konseling Islam terhadap siswa 3.Mengetahui hasil konsep nilai budi pekerti dalam layanan bimbingan konseling Islam terhadap siswa. Hasil penelitian ini merupakan Implementasi konseling Islami dalam pembinaa akhlak di MTSN 1 Kuala Tungkal Kabupaten Tanjug Jabung Barat terlaksana dan menunjukkan hal yang positif. Hal tersebut dapat dilihat dari perubahan-perubahan yang terjadi dari setiap siswa. Secara perlahan siswa mampu mengerjakan nasihat, arahan dan penjelasan dari guru BK, sehingga masalah yang pernah dilakukan tidak terjadi lagi. Siswa yang telah mengikuti konseling Islami, mereka lebih mengenal jati diri sebagai manusia yang memiliki budi pekerti yang baik dalam kehidupan sehari-hari termasuk lingkungan sekolah, keluarga dan lingkungan tempat tinggal.